Educating children with exceptionalities - Karen L. Freiberg (McGraw-Hill Higher Education, 2007)
This Nineteenth Edition of ANNUAL EDITIONS: EDUCATING CHILDREN WITH EXCEPTIONALITIES provides convenient, inexpensive access to current articles selected from the best of the public press. Organizational features include: an annotated listing of selected World Wide Web sites; an annotated table of contents; a topic guide; a general introduction; brief overviews for each section; a topical index; and an instructor's resource guide with testing materials